Eastman Kodak Co. managing information systems through strategic alliances. (1991)
This is a Spanish version. In January 1988, Colby Chandler, Kodak CEO, created the Corporate Information Systems (CIS) and appointed Katherine Hudson head. She at once became the first head of IT and first woman corporate vice president in the company. Throughout 1989, Hudson inaugurated a series of organizational initiatives that not only would dramatically change the IT function within Kodak, but would rock the industry. She outsourced data center operations, telecommunications services, and personal computer support to IBM, DEC, and Business Land, respectively. Case presents the complexities in managing information systems through partnerships.